2007
DOI: 10.1002/crat.200610806
|View full text |Cite
|
Sign up to set email alerts
|

Notes on some supposed transitions of the phase NiBi

Abstract: X-Ray, DSC and magnetic susceptibility measurements were performed with NiBi specimens in the interval from room temperature to 700 K. The hypothesis of solid-state transitions in this phase was not confirmed. Thermal and magnetic effects are observed, but they are due to the existence of small amount of phases others than NiBi (i.e. unreacted Ni and Bi).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Concerning the modeling of the nonstoichiometric NiBi phase, in all previous optimizations [1,3,5] it was accepted that the bismuth is slightly predominant constituent. This is confirmation of the results of Feschotte and Rosset [9] and the later experimental investigations of Vassilev et al [1,2]. There are, however, differences concerning the thermodynamic descriptions of this compound.…”
Section: ____________________supporting
confidence: 87%
See 1 more Smart Citation
“…Concerning the modeling of the nonstoichiometric NiBi phase, in all previous optimizations [1,3,5] it was accepted that the bismuth is slightly predominant constituent. This is confirmation of the results of Feschotte and Rosset [9] and the later experimental investigations of Vassilev et al [1,2]. There are, however, differences concerning the thermodynamic descriptions of this compound.…”
Section: ____________________supporting
confidence: 87%
“…For a contemporary survey of the related experimental studies one could refer to Vassilev et al [1][2][3]. A detailed assessment (based on ref.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of enthalpies of formations, activities, phase equilibria and thermodynamic optimizations [1,15e 25] of this system have been performed but ambiguities about the thermochemical properties persist [24]. Thus, the purpose of this work is measuring enthalpies of formation of solid and liquid CoeSn alloys and collateral phase diagram studies.…”
Section: Introductionmentioning
confidence: 99%
“…% Bi. Later, Feschotte and Rosset [16] as well as Vassilev et al [10,11] have found that the compound NiBi is almost equiatomic. Further details are available in a number of specialized handbooks [17][18][19][20][21] The pure stable metallic phases: rhombohedral bismuth (Bi) and face-centered cubic nickel (fcc-Ni) were identified following XRD data of JCPDS cards nos.…”
Section: Resultsmentioning
confidence: 97%
“…In this aspect, experimental studies and thermodynamic optimization of this system have recently been done by Vassilev et al [6,10,11]. Moreover, Teyeb et al [12] synthesized NiBi nanosized particles using organic precursors but these are relatively expensive compared to the inorganic reagents.…”
Section: Introductionmentioning
confidence: 99%